Leveraging CSR To Promote Inclusive and Sustainable Development: Evidence from CSR Reporting of NSE Companies - Roy, Prantik; Uday Krishna Mittra (Indonesian Management and Accounting Research, 2024)
The Companies Act (2013) in India has brought about manifold changes to the regulation of companies. The provisions of new law require giving emphasis on corporate social causes marking a significant departure from previous mere voluntary guidelines. As a result of these provisions, India will now be recognized as world’s CSR “frontrunner” nation. Section 135 of the Act read with Schedule VII likely to better promote the process of the link between CSR and broad-based inclusive and sustainable development goals. Thus, a total of 34 out of top 100 companies listed in NSE were chosen as samples for analyzing their CSR practices and reporting initiatives. Content Analysis Method is used to extract data from annual reports of companies. Descriptive and inferential statistics such as, t-test, ANOVA, correlation and regression were used to examine data. A CSR practices and reporting grid and a model were proposed in study respectively for developing relevant score and performing regression analysis. The findings show that Indian companies are making significant contributions toward achieving the goals of inclusive and sustainable development through their efforts to implement CSR as evidenced form their CSR reporting.